A grid interconnected nested neutral-point clamped inverter with voltage synchronization using synchronous reference frame controller - Sirisha Bogimi (International Journal of Applied Power Engineering (IJAPE), 2021)
Nested neutral-point clamped multi level inverter with inter connection to grid through the synchronous reference frame (SRF) controller for synchronization of voltage to the grid is demonstrated. The system's main feature is that voltage stress in each inverter switching device is kept to a minimum, and redundant inverter switching states are utilised for neutral point and flying capacitor voltage balancing with sinusoidal pulse-width modulation (PWM) technique, synchronisation to grid voltages, and power injection with low harmonic generation. The inverter receives its input from a photovoltaic (PV) source that is coupled to DC-DC booster converters that are regulated by the maximum power point (MPP) tracking incremental conductance algorithm to maintain a constant dc voltage. The system is examined under various load conditions with MATLAB/Simulink model.